Gentamicin compared with ceftriaxone for the treatment of gonorrhoea (G-ToG): a randomised non-inferiority trial. Issue 10190 (22nd June 2019) - Ross, Jonathan D C; Brittain, Clare; Cole, Michelle; Dewsnap, Claire; Harding, Jan; Hepburn, Trish; Jackson, Louise; Keogh, Matthew; Lawrence, Tessa; Montgomery, Alan A; Roberts, Tracy E; Sprange, Kirsty; et al.
Summary: Background: Gonorrhoea is a common sexually transmitted infection for which ceftriaxone is the current first-line treatment, but antimicrobial resistance is emerging. The objective of this study was to assess the effectiveness of gentamicin as an alternative to ceftriaxone (both combined with azithromycin) for treatment of gonorrhoea. Methods: G-ToG was a multicentre, parallel-group, pragmatic, randomised, non-inferiority trial comparing treatment with gentamicin to treatment with ceftriaxone for patients with gonorrhoea. The patients, treating physician, and assessing physician were masked to treatment but the treating nurse was not. The trial took place at 14 sexual health clinics in England. Adults aged 16–70 years were eligible for participation if they had a diagnosis of uncomplicated genital, pharyngeal, or rectal gonorrhoea. Participants were randomly assigned to receive a single intramuscular dose of either gentamicin 240 mg (gentamicin group) or ceftriaxone 500 mg (ceftriaxone group). All participants also received a single 1 g dose of oral azithromycin. Randomisation (1:1) was stratified by clinic and performed using a secure web-based system. The primary outcome was clearance of Neisseria gonorrhoeae at all initially infected sites, defined as a negative nucleic acid amplification test 2 weeks post treatment. Primary outcome analyses included only participants who had follow-up data, irrespective of the baseline visit N gonorrhoeae test result. The margin used to establish non-inferiority was a lower confidence limit of 5% for the risk difference. This trial is registered with ISRCTN, number ISRCTN51783227. Findings: Of 1762 patients assessed, we enrolled 720 participants between Oct 7, 2014, and Nov 14, 2016, and randomly assigned 358 to gentamicin and 362 to ceftriaxone. Primary outcome data were available for 306 (85%) of 362 participants allocated to ceftriaxone and 292 (82%) of 358 participants allocated to gentamicin. At 2 weeks after treatment, infection had cleared for 299 (98%) of 306 participants in the ceftriaxone group compared with 267 (91%) of 292 participants in the gentamicin group (adjusted risk difference −6·4%, 95% CI −10·4% to −2·4%). Of the 328 participants who had a genital infection, 151 (98%) of 154 in the ceftriaxone group and 163 (94%) of 174 in the gentamicin group had clearance at follow-up (adjusted risk difference −4·4%, −8·7 to 0). For participants with a pharyngeal infection, a greater proportion receiving ceftriaxone had clearance at follow-up (108 [96%] in the ceftriaxone group compared with 82 [80%] in the gentamicin group; adjusted risk difference −15·3%, −24·0 to −6·5). Similarly, a greater proportion of participants with rectal infection in the ceftriaxone group had clearance (134 [98%] in the ceftriaxone group compared with 107 [90%] in the gentamicin group; adjusted risk difference −7·8%, −13·6 to −2·0). Thus, we did not find that a single dose of gentamicin 240 mg was non-inferior to a single dose of ceftriaxone 500 mg for the treatment of gonorrhoea, when both drugs were combined with a 1 g dose of oral azithromycin. The side-effect profiles were similar between groups, although severity of pain at the injection site was higher for gentamicin (mean visual analogue pain score 36 of 100 in the gentamicin group vs 21 of 100 in the ceftriaxone group). Interpretation: Gentamicin is not appropriate as first-line treatment for gonorrhoea but remains potentially useful for patients with isolated genital infection, or for patients who are allergic or intolerant to ceftriaxone, or harbour a ceftriaxone-resistant isolate. Further research is required to identify and test new alternatives to ceftriaxone for the treatment of gonorrhoea. Funding: UK National Institute for Health Research.